PENGARUH KONFLIK PERAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN TETAP PADA PT. PLN (PERSERO) WILAYAH SULSEL, SULTRA DAN SULBAR AREA BAUBAU - SRI HARTINA, ELISA (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to analyze the influence of role conflict and job satisfaction on the performance of permanent employees at PT. PLN (Persero) Region of South Sulawesi, Sultra and Sulbar Area Baubau. The sample used in this research take saturated sample technique that is amounted to 36 permanent employees. Questionnaire calculation returns all. The analysis technique used is Structural Equation Model. Partial Least Square with the help of Smart Software PLS3.0. The results of this study indicate that role conflict has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance.” Keywords: Role Conflict, Job Satisfaction, Employee Performance